SAT0205 A CYTOKINE "SCAR SIGNATURE" CHARACTERIZES PATIENTS WITH FATIGUE IN SYSTEMIC LUPUS ERYTHEMATOSUS AND SJOGREN'S SYNDROME. (June 2019) - Rossi, Carlo Maria; Horisberger, Alice; Moi, Laura; Ohimiti, Khalid; Perreau, Mathieu; Pantaleo, Giuseppe; Ribi, Camillo
Abstract : Background: Fatigue is highly prevalent in systemic lupus erythematosus patients (SLE) and primary Sjoegren's syndrome (pSS) and represents one of its unmet needs.[1] Its pathogenesis is multifactorial, with the activity of the underlying disease exerting a prominent role, along with psychological factors and co-morbid conditions. Previous studies evaluating fatigue and cytokines in patients with SLE and pSS have yielded inconclusive results. Objectives: We aimed to evaluate patient-reported outcome measures reflecting fatigue and their correlation to serum cytokines in patients with SLE and pSS and healthy volunteers (HV). A panel of circulating cytokines, chemokines and growth factors was compared between groups, correlated to the level of fatigue and within SLE and pSS to global disease activity. The objective was to identify cytokines reflecting the degree of fatigue, which could be exploited as biomarkers and therapeutic targets. Methods: We performed a cross-sectional study on subjects included in the Swiss SLE Cohort Study (SSCS). All subjects were evaluated clinically and had a serum sample taken. Fatigue was assessed by FAS (Fatigue Assessment Scale) and by the vitality subscale (VT) of the Medical Outcomes Study 36-Items Short Form Healthy Survey. Clinical activity in SLE and pSS patients was determined by a 4-point Likert-scale Physician's Global Assessment (PGA). SLE activity was assessed with the SLE Disease Activity Index score with the Safety of Estrogens in SLE National Assessment modification (SELENA-SLEDAI). Serum cytokines were assessed by multiplex bead array analysis (ProcartaPlex, Thermofischer Scientific, USA). P values were adjusted for multiple comparisons. Results: Fifty-six patients with SLE, 18 with pSS and 18 healthy volunteers (HV) were included between November 2015 and June 2016. There were no significant differences between groups regarding to age, gender and body mass index (BMI). FAS and VT correlated strongly (Spearman's rho -0.87, p<0.01). FAS was significantly higher in patients than in healthy individuals (median FAS 23 [16-31], 28[20.5-35], 17 [15-27] in SLE, pSS and HV respectively; p=0.02). Patients with SLE and pSS displayed higher serum levels of interferon (IFN)-gamma (median [IQR] 10.29 [4.94-15.25] pg/mL in SLE, 9.64 [6.25-13.86] pg/mL, undetectable in HV; p <0.01). Interleukin (IL)-10 also was only detected in pSS and SLE. Hepatocyte growth factor (HGF) was more expressed in patients than in controls (p= 0.01). The levels of most other cytokines (IFN-alpha, IL-1 alpha, IL-2, IL-4, IL-6, IL-17, IL-21 and IL-23) were not detectable. Only HGF displayed a significant correlation with FAS (P Pearson 0.29, p< 0.01). Conclusion: Patients with SLE and pSS display a molecular pattern of chronic inflammatory conditions, with higher serum levels of IFN-gamma, IL-10 and HGF. The latter two are both involved in regeneration and tissue repair ("scar signature")[2]. HGF levels correlated independently with the degree of fatigue. More studies are needed to understand the role of this pleiotropic growth factor in self-perceived fatigue in SLE and pSS. References: [1] Chaigne B, Chizzolini C, Perneger T, Trendelenburg M, Huynh-Do U, Dayer E, Stoll T, von Kempis J, Ribi C, Swiss Systemic Lupus Erythematosus Cohort Study G: Impact of disease activity on health-related quality of life in systemic lupus erythematosus - a cross-sectional analysis of the Swiss Systemic Lupus Erythematosus Cohort Study (SSCS). BMC Immunol 2017, 18(1):17. [2] Fukushima T, Uchiyama S, Tanaka H, Kataoka H: Hepatocyte Growth Factor Activator: A Proteinase Linking Tissue Injury with Repair. Int J Mol Sci 2018, 19(11). Disclosure of Interests: None declared